Replacing discontinuous change with continuous improvement - Influencing factors on organizations’ capability to continuously improve - Hermansson, Mattias; Karlsson, Mikael (My University, 2016)
Akademiska Hus has implemented several drastic changes recent years and is currently performing an organizational restructuring. One underlying reason for this restructuring is issues with consistency within the organization. The purpose of this thesis is to bring forth potential countermeasures to enhance consistency, and further aims to provide insights in how to establish a culture, and the tools necessary for a steady foundation, in which continuous improvements can prosper, and thus prevent the need for major changes in the future. The findings indicate that Akademiska Hus has great potential to reach further in the area of continuous improvements as they already possess vital elements required for higher levels. However, further efforts in including a larger portion of the organization in the innovation process is needed. This could be done by implementing a reward and recognition system, and by strategically aligning every-day tasks with the overall organizational targets. A key to do so is to implement a well-structured performance measurement system to monitor and steer the direction of improvements. Such system can further contribute to a greater understanding of organizational targets amongst employees by identifying, and communicating strategically important areas. This thesis further investigates potential contributions partnering can bring to the organization in the area of continuous improvements. Partnering is essentially a contracting form with the aim to enhance collaboration between actors in the construction sector. The study identifies several benefits partnering can bring with it. Close collaboration can enable better communication and create mutually agreed goals and visions for the project organization. Further are the possible trade-offs between actors, such as the ability to share resources and solutions perceived as potential contributors to increase overall continuous improvements. The thesis conclude by recommending the implementation of an adequate performance measurement system to enable monitoring of the actual impact partnering brings with it compared to traditional contracting forms.
Keywords: Samhällsbyggnadsteknik; Civil Engineering